Sound Symbolism in English and Japanese - Dewi Nurmala; Mulyadi Mulyadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
The objective of this research is to analyze the types of sound symbolism in English and Japanese. The data used is derived from the research results of sound symbolism in English and Japanese. The method used is a qualitative method. Data collection and technique of data analysis are using data condensation techniques, data presentation and conclusion drawing. From the results of the analysis, it was found that there are four types of sound symbolism in English, namely physical, imitation, synthetic and conventional sound symbolism, while in Japanese sound symbolism belongs to the onomatopoeic category. There are five types of onomatopoeic, namely giongo, giseigo, gitaogo, giyougo, and gijougo. The phonemes involved in sound symbolism in English are dominated by the vowel /a,o/ while in Japanese it is dominated by the vowel /e,a/.